Energy management in industrial complexes : a systems approach - Panda, Haribandhu; Mohanty, Brahmanand; Shrestha, Ram M.; Mora, Jean Claude; Danish International Development Assistance (DANIDA) (Bangkok : Asian Institute of Technology, 1992)
A general personal compute r based model of Integrated Energy System for Industrial Estates (IESIE) has been developed as a prefeasibility tool which addresses the total energy concept by combining a set of CHP plant(s), boiler, vapour compression chiller and vapour absorption chillers, national grid and utility transportation system. The core of the general model is the Linear programming (LP) model which takes into account the changing dema nd pattern of variou s loa ds and their tariffs, standby c harge of electricity , fuel price , equipment costs, land cost, depreciation, O&M expenses, interest rate, taxes,etc. The output of the LP model y ields the minimum total operating cost, optima l sizes of the equipment and their respective operational sch edules. The economic model does the cash flow analysis for a number of years and shows whether the project will yield required r ate of return to be economically viable. The hot utility and cold utility transportation model finds the economically minimum pipe size considering installation cost, h eat loss/ gain cost and pumping cost. The heat balance model finds the thermal cycle equipment sizes as well as the variation of heat to powe r ratio with load. Simulation have been carried out u sing the mode l con sidering a numbe r of load patterns with the prevailing cost factors in India. An after tax IRR of 20 percent was found for sites hav ing load factors g reater than 0.6 a nd a nd 10 km utility transportation distance. It was found economical to tra nsport steam and locally generate cold utility to r e duce transportation cost. An industrial estate was identified to apply the IESIE concept as a case study. Using the energy demand patterns of the various industries in this estate, and assuming the existing electricity to fuel price ratio, 83 percent buyback rate, 10 km utility transportation distance, 6 percent energy price escalation per annum and debt to equity ratio of 1, the after tax IRR was found to be 11.2 percent. Considering the net saving in primary energy to the tune of 30 percent and subsequent environmental b e nefits in the form of reduced emissions the project can be made v iable by combining a package of measures covering buyback rate, fuel price, en ergy price escalation rate, interest rate and other financial and fiscal incentives. A s urvey con clude d that given the reliability and economic pricing, industries were willing to cooperate in the integrated ener gy system. However a number of institutional, administrative, legal, t echnical a nd information barriers were identifie d as hampering the impleme ntation of such IESIE projects.
A thesis submitted in partial fulfillment of the requirement for the degree of Master of Engineering
Thesis (M.Eng.) - Asian Institute of Technology
Keywords: Industrial districts -- Energy conservation